STING agonist delivery by lipid calcium phosphate nanoparticles enhances immune activation for neuroblastoma - Bo Feng; Xiao Lu; Guangqin Zhang; Libo Zhao; Dong Mei (Acta Materia Medica)
Neuroblastoma (NB) is a common solid tumor in children and infants, the formation and regression of which is closely linked to the tumor-host immune relationship. Stimulator of interferon genes (STING) agonists, particularly cyclic dinucleotide (CDN), have promising potential in NB therapy by generating innate and adaptive immune stimulation, thus leading to tumor control. CDN delivery in vivo is challenging due to the negative charge, hydrophilicity, and susceptibility to degradation by phosphodiesterase, which hinders the effectiveness of CDN. Thus, our study proposed four methods to load CDN into liposomes, using 2′,3′-cGAMP as the model drug. Lipid nanoparticles were prepared, followed by physicochemical characterization. Subsequently, cellular inhibition and immune stimulation were investigated. As a result, lipid calcium phosphate nanoparticles (LCP-NPs) possessed the highest encapsulation efficiency among the four preparation methods, with a diameter of 82.57±3.72 nm. LCP-NPs maintained size stability under refrigeration conditions at 4°C within 48 h. The surface of the liposome was positively charged. Compared to free cGAMP, LCP-NPs resulted in a slower release, enhanced cytotoxicity against tumor cells, greater activation of the cGAS-STING pathway, and increased expression of the immune factors. Taken together, these findings clearly demonstrated the effectiveness of the liposomal delivery system for cGAMP and provided a promising strategy for the treatment of NB.